(untitled) (Italian Journal of Public Health, 2008)
Background: Malignant melanoma (MM) can be readily treated in its earliest stages: survival rate, when detected early, is up to 95,0%. This justifies investigations on contributive factors and measures for precocious detection of skin tumors to improve early detection and to increase survival rates. The purpose of this survey was to collect information about knowledge, attitudes and behaviors on prevention in relation to skin checks for early signs of skin cancer on a sample of secondary school students and teachers. Methods: A sample of secondary school students and teachers from Palermo, was recruited using the cluster sampling method. A self-administered questionnaire, consisting of twenty four multiple choice questions was used as the survey instrument. Statistical analysis of data obtained was performed using Openstat software. Results: The research showed a good level of awareness about skin cancer risk factors, which seemed to be strictly correlated with age. On the contrary, practice of skin self-examination (SSE) is not as widespread, and only 4,8% regularly checked the parts of their bodies most exposed to the risk of developing skin cancer. Both students and teachers indicated that school-based health education programs are the best way to promote the importance of prevention. Conclusions: In many countries mortality is not increasing at the same rate as incidence for MM. The practice of SSE may play a vital role in improving early detection and survival rates. Therefore, school interventions to promote knowledge of the benefits of regular SSE should be implemented.